Effect of Individualism on Online User Ratings: Theory and Evidence. Issue 5 (20th October 2019) - Banerjee, Somnath; Chai, Linlin
Abstract: This research examines the effect of individualism on online user ratings. We develop a theory based on expectation disconfirmation theory and prospect theory, and posit that user review ratings by consumers from individualistic cultures (e.g., America), as compared to collectivistic cultures (e.g., China), are likely to be lower, and the effect is moderated by customer-based brand equity and experience of premium product variants (e.g., business class travel). We test our hypotheses on a data set gathered from online user reviews by customers from 166 countries for airlines across the world and find support. In addition, customer-based brand equity and experience of premium product variants have positive direct effects on user rating valence. We also test our hypotheses on recommendation intent of users and control for fixed effects and find support. Managerial implications and future research avenues are discussed.